Pemberian Makan Pada Balita dan Konsumsi Zat Mikro Saat Ibu Nifas dengan Status Gizi Balita - Yena Wineini Migang; Ketut Resmaniasih; Evan Kristanus Migang (Jurnal Kesehatan Komunitas, 2022)
Stunting is at risk of inhibiting toddler brain development. One of the stunting factors is the consumption of micronutrients when the mother is giving birth and the consumption of food when she is a toddler. The aim of the study was to determine the relationship between infant feeding and micronutrient consumption during parturition with the nutritional status of children under five. Cross sectional design purposive sampling technique, chi square analysis. Respondents were 168 mothers of toddlers and toddlers aged 7 months to 36 months in the working area of ​​Pulang Pisau Health Center, Edison Jaar Health Center, and Tamiang Layang Health Center. The results of the study, the highest percentage of maternal education was SMA (67.3%). Nutritional status of children under five nutritional status is not stunting (85.7%). Toddlers do not get IMD immediately after birth (89.9%), exclusive breastfeeding (58.9%), toddlers drink vitamin A (87.5%), mothers drink vitamin A (72.6%), mothers do not drink Fe tablets (61.9%). Toddlers did not take deworming medicine (76.8%). There is a relationship between toddlers taking vitamin A tablets with the nutritional status of toddlers where the P value (0.008) with the contingency coefficient (C) 0.202.